Epidemiological typing of isolates from an outbreak of infection with multidrug-resistant Enterobacter cloacae by repetitive extragenic palindromic unit b1-primed PCR and pulsed-field gel electrophoresis. - Shi, Z Y (1996)
An outbreak of multidrug-resistant Enterobacter cloacae infection lasted for 4 months in a neonatal intensive care unit (NICU). Forty-six isolates from the NICU and 20 epidemiologically unrelated strains were characterized by pulsed-field gel electrophoresis (PFGE) and repetitive extragenic palindromic unit b1-primed PCR (REPUb1-PCR) typing. The PFGE patterns after XbaI restriction of the bacterial DNA were analyzed by computer software (Gelcompar) using the UPGMA (unweighted pair group method with arithmetic averages) clustering method and the Dice coefficient. The 46 isolates from the NICU were classified by PFGE typing into five clusters: A (further classified into 7 subtypes, A1 to A7), B, C, D, and E. This outbreak was attributed to multiple genetically related strains of cluster A which had a similarity of 85.8% +/- 4.6%. The minor band differences among strains of cluster A were probably due to minor genetic mutations. The type A1 and A3 strains were isolated from the clinical specimens of patients and hands of nurses. It was probable that these outbreak strains were transmitted among patients via the hands of personnel. REPUb1-PCR typing of the 46 isolates also demonstrated five types, in agreement with results obtained by the PFGE technique, but could not detect the minor mutations among the cluster A strains. Twenty epidemiologically unrelated strains were well distinguished by both PFGE and REPUb1-PCR typing. We conclude that PFGE is a highly discriminatory but time-consuming method for epidemiological typing of E. cloacae and that REPUb1-PCR is a more rapid method with good reproducibility and discriminatory power comparable to that of PFGE.